Readout circuit design and noise analysis of active pressure sensing for flexible and wearable medical applications - Li, Si (2017)
The advancement in sensing materials has led to the growth of the sensing technologies in flexible and wearable medical applications, especially the pulse and blood pressure monitoring. These technologies offer many key advantages and hence their popularity in recent years. In this dissertation, the author has reviewed three typical sensing technologies, including piezoelectric sensing, capacitive sensing and piezoresistive sensing. The operation principle and pros / cons of the technologies are investigated. Piezoelectric sensing is selected to be used in this project, after a comparison of the sensing performance. A commercial sensor is consisting of a sensor device and an interface circuit, and the key component of the readout circuit is the op amp. In this project, the author contributes to the transistor-level circuit design for op amp. The op-amp design phase includes hand calculations of the op-amp parameters followed by simulations using Cadence tools. Followed by a proper design procedure, a series of parameters are achieved: open-loop gain is over 1700, slew rate is more than 8 V/μs and input offset voltage is about 720 μV. A noise model of the op amp is also analyzed, and some approaches to reduce noise are proposed. Next, the author’s work focuses on the piezoelectric pressure sensor; two conditioning modes had been evaluated; the voltage mode configuration is then selected for the interface circuit design. Apart from transistor-level circuit design stated previously, a board-level circuit design for sensor interface circuit is also conducted. In the board-level circuit design, board-level simulations and system simulations are conducted to ensure the closed-loop circuit works well. A discreet hardware PCB is built and measurement test is carried out. The measured results match with the simulation results, hence the performance of the circuit is functionally proven.